2003
DOI: 10.1111/j.1939-1676.2003.tb02517.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Chlamydophila felis and Feline Herpesvirus 1 in Cats with Conjunctivitis in Northern Italy

Abstract: The prevalence of Chlamydophila felis and feline herpesvirus 1 (FHV-1) infection in cats with conjunctivitis in northern Italy was investigated by conventional polymerase chain reaction (PCR) testing. In cats with conjunctivitis, C felis and FHV-1 were detected in 14 of 70 (20%) and in 23 of 70 (33%) animals, respectively. None of the 35 control cats were positive for C felis, whereas 7 (20%) of these cats were positive for FHV-1. Mixed infections were present in 5 of 70 cats (7%). Cats positive for C felis we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 48 publications
3
46
1
Order By: Relevance
“…In Korea, a total of 78 cats without ocular and upper respiratory tract disease were examined and all specimens were negative for C. felis in PCR (Kang & Park 2008). In the present study, from nine positive samples, three were from vaccinated cats, contradicting previous reports (Rampazzo et al 2003) that showed that none of the vaccinated cats were PCR-positive for this microorganism. Thus, the objective of active immunization against C. felis is to reduce the severity of clinical signs of the disease (Wasmoen et al 1992), but not to prevent shedding of the organism .…”
Section: Virus Reviews and Research 15 Nr 2 2010contrasting
confidence: 98%
See 1 more Smart Citation
“…In Korea, a total of 78 cats without ocular and upper respiratory tract disease were examined and all specimens were negative for C. felis in PCR (Kang & Park 2008). In the present study, from nine positive samples, three were from vaccinated cats, contradicting previous reports (Rampazzo et al 2003) that showed that none of the vaccinated cats were PCR-positive for this microorganism. Thus, the objective of active immunization against C. felis is to reduce the severity of clinical signs of the disease (Wasmoen et al 1992), but not to prevent shedding of the organism .…”
Section: Virus Reviews and Research 15 Nr 2 2010contrasting
confidence: 98%
“…Detection of C. felis genome using polymerase chain reaction (PCR) in cats ranged from 1.1 to 26.9% (Mcdonald et al 1998, Sykes et al 1997, Sykes et al 1999, Mochizuki et al 2000, Iwamoto et al 2001, Rampazzo et al 2003, Von Bomhard et al 2003, Marsílio et al 2004, Low et al 2007. In others studies, C. felis genome was not detected by PCR and real-time PCR in cats (Kang & Park 2008, Veir et al 2008, Sjödahl-Essén et al 2008.…”
Section: Virus Reviews and Research 15 Nr 2 2010mentioning
confidence: 99%
“…Chlamydophila spp., especially Chlamydophila felis, can occur in cats with clinical signs as well as in animals without any manifestation of disease; however some studies have noted that the presence of Chlamydophila was significantly associated with conjunctivitis (p = 0.04) (Rampazzo et al 2003). A variety of tests and methods are available for the diagnosis of Chlamydophila infection.…”
Section: Discussionmentioning
confidence: 99%
“…It is a cause of ocular and upper respiratory tract disease in cats, characterized by conjunctivitis, sneezing, fever, transient inappetence, and mild nasal discharge. 276,280 There are reports of zoonotic C. felis infection from cats, 281 -287 but these are small in number and generally weak. 276 Transmission is presumably through direct contact with infected animals and fomites, and potentially through aerosols.…”
Section: Chlamydophila F Elismentioning
confidence: 99%